2015
DOI: 10.1038/ncomms9485
|View full text |Cite
|
Sign up to set email alerts
|

Entropy-stabilized oxides

Abstract: Configurational disorder can be compositionally engineered into mixed oxide by populating a single sublattice with many distinct cations. The formulations promote novel and entropy-stabilized forms of crystalline matter where metal cations are incorporated in new ways. Here, through rigorous experiments, a simple thermodynamic model, and a five-component oxide formulation, we demonstrate beyond reasonable doubt that entropy predominates the thermodynamic landscape, and drives a reversible solid-state transform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

34
1,484
1
9

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 2,170 publications
(1,528 citation statements)
references
References 41 publications
(44 reference statements)
34
1,484
1
9
Order By: Relevance
“…Following up on the results of Rost et al, 15 Berardan et al reported that the single-phase, entropic rocksalt structure of J14 is maintained with the addition of Li and Li co-incorporated with Ga as substitutional (rather than interstitial) defects. 16,17 The former is commonly associated with a þ1 formal charge state, and so the authors suggest charge compensation involving oxidation of Co þ2 to Co þ3 and/or creation of O vacancies.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Following up on the results of Rost et al, 15 Berardan et al reported that the single-phase, entropic rocksalt structure of J14 is maintained with the addition of Li and Li co-incorporated with Ga as substitutional (rather than interstitial) defects. 16,17 The former is commonly associated with a þ1 formal charge state, and so the authors suggest charge compensation involving oxidation of Co þ2 to Co þ3 and/or creation of O vacancies.…”
Section: Introductionmentioning
confidence: 99%
“…There are clearly tremendous possibilities for designing materials of this type with potentially interesting and unique properties and applications. [15][16][17] Zhang et al 3 demonstrated that the stability of nonoxide MHEAs can be reasonably predicted based on two empirical parameters that can be derived from the component elements, a measure of the differences in atomic radii and the mixing enthalpy for a solid solution. In addition, to enhance the free energy of the MHEAs the entropy of mixing should be maximized, which occurs for equi-molar concentrations.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This result has been shown most directly in highentropy oxides. 38 This new perspective overturns many decades of neglect, where enthalpies have been the primary focus and the role of configurational entropy has never been systematically evaluated in phase selection. Establishing the role of configurational entropy as an adjustable parameter in phase engineering gives a more balanced, mature perspective that is a major success from the early HEA years.…”
Section: Discussionmentioning
confidence: 99%
“…However, only doped, co-doped and binary ceramics have been extensively studied, while the area of equimolar, multicomponent ceramics has been a largely unexplored field until recently [1]- [3]. In this investigation, a multicomponent nanocrystalline ceramic oxide, (Co,Cu,Mg,Ni,Zn)O, was synthesised with the primary intention of studying the type and stability of the phases formed with systematically varying zinc oxide content.…”
mentioning
confidence: 99%